Peak knee biomechanics and limb symmetry following unilateral anterior cruciate ligament reconstruction: Associations of walking gait and jump-landing outcomes. (March 2018) - Pfeiffer, Steven J.; Blackburn, J. Troy; Luc-Harkey, Brittney; Harkey, Matthew S.; Stanley, Laura E.; Frank, Barnett; Padua, Darin; Marshall, Stephen W.; Spang, Jeffrey T.; Pietrosimone, Brian
Abstract: Background: Aberrant walking-gait and jump-landing biomechanics may influence the development of post-traumatic osteoarthritis and increase the risk of a second anterior cruciate ligament injury, respectively. It remains unknown if individuals who demonstrate altered walking-gait biomechanics demonstrate similar altered biomechanics during jump-landing. Our aim was to determine associations in peak knee biomechanics and limb-symmetry indices between walking-gait and jump-landing tasks in individuals with a unilateral anterior cruciate ligament reconstruction. Methods: Thirty-five individuals (74% women, 22.1 [3.4] years old, 25 [3.89] kg/m 2 ) with an anterior cruciate ligament reconstruction performed 5-trials of self-selected walking-gait and jump-landing. Peak kinetics and kinematics were extracted from the first 50% of stance phase during walking-gait and first 100 ms following ground contact for jump-landing. Pearson product-moment (r) and Spearman's Rho (ρ) analyses were used to evaluate relationships between outcome measures. Significance was set a priori ( P ≤ 0.05). Findings: All associations between walking-gait and jump-landing for the involved limb, along with the majority of associations for limb-symmetry indices and the uninvolved limb, were negligible and non-statistically significant. There were weak significant associations for instantaneous loading rate (ρ = 0.39, P = 0.02) and peak knee abduction angle (ρ = 0.36, p = 0.03) uninvolved limb, as well as peak abduction displacement limb-symmetry indices (ρ= − 0.39, p = 0.02) between walking-gait and jump-landing. Interpretation: No systematic associations were found between walking-gait and jump-landing biomechanics for either limb or limb-symmetry indices in people with unilateral anterior cruciate ligament reconstruction. Individuals with an anterior cruciate ligament reconstruction who demonstrate high-involved limb loading or asymmetries during jump-landing may not demonstrate similar biomechanics during walking-gait. Highlights: Altered kinetics and kinematics observed following anterior cruciate ligament reconstruction may be task dependent. Individuals with greater peak biomechanics during walking do not demonstrate greater peak biomechanics during jump-landing. Asymmetrical walking does not correlate with asymmetrical jump-landing following anterior cruciate ligament reconstruction.